The mechanism of biomineralization: Progress in mineralization from intracellular generation to extracellular deposition - Xin Yan; Qi Zhang; Xinyue Ma; Yewen Zhong; Hengni Tang; Sui Mai (Elsevier, 2023)
Biomineralization is a highly regulated process that results in the deposition of minerals in a precise manner, ultimately producing skeletal and dental hard tissues. Recent studies have highlighted the crucial role played by intracellular processes in initiating biomineralization. These processes involve various organelles, such as the endoplasmic reticulum(ER), mitochondria, and lysosomes, in the formation, accumulation, maturation, and secretion of calcium phosphate (CaP) particles. Particularly, the recent in-depth study of the dynamic process of the formation of amorphous calcium phosphate(ACP) precursors among organelles has made great progress in the development of the integrity of the biomineralization chain. However, the precise mechanisms underlying these intracellular processes remain unclear, and they cannot be fully integrated with the extracellular mineralization mechanism and the physicochemical structure development of the mineralization particles. In this review, we aim to focus on the recent progress made in understanding intracellular mineralization organelles' processes and their relationship with the physicochemical structure development of CaP and extracellular deposition of CaP particles.